Creed : What Christians Believe and Why. - Hamilton, Adam, 1964- (Nashville : Abingdon Press, 2016)
Affirming Our Faith at Lent and Easter.
Cover; Half title; Title; Copyright; Dedication; Contents; Introduction: I Believe; 1. God; 2. Jesus Christ; 3. The Holy Spirit; 4. The Church and the Communion of Saints; 5. The Forgiveness of Sins; 6. The Resurrection of the Body; Appendix: The Creeds of the Church; Notes; Bibliography; Acknowledgments.
Print version record.
Includes bibliographical references.
Keywords: Apostles' Creed; Bible -- Study and teaching; Theology, Doctrinal -- Popular works; RELIGION -- Christianity -- Catechisms; Apostles' Creed; Bible; Study skills; Theology, Doctrinal; Electronic books; Popular works